Consumer acceptance of the usage of artificial intelligence in the banking sector - Hidas, Réka Emma (2024)
In the past years, artificial intelligence (AI) technologies have become rapidly integrated into the banking sector, thus understanding the factors that influence customers to accept the usage of these innovations is crucial for financial institutions. AI offers huge transformative potential, as it can enhance operational efficiency, improve consumer service, or strengthen security. However, there is limited research on how consumers perceive and adopt these technologies, especially from a customer experience (CX) perspective. This gap in understanding presents a challenge for banks that are trying to fully leverage AI in their customer-facing services. This study aims to investigate the key factors that are influencing consumer acceptance of AI technologies in banking, with a focus on awareness, trust in electronic security, customer experience, and demographic factors, specifically age. The results revealed that the most significant driver for adoption is the perceived trust towards electronic security. Age also has a huge influence, as younger customers appeared to be more inclined to embrace AI services compared to older generations. Contrary to expectations, neither customers’ awareness of using AI technologies nor customer experience had a statistically significant impact on AI acceptance.